Surgical complications in pediatric patients with complicated acute appendicitis in open and laparoscopic surgeries in a national referral center - Paz Soldán Mesta, Carolina Fabiola (2020)
Objective: To determine the incidence and type of complications after an appendectomy in patients with appendicitis complicated by peritonitis in relation to the type of surgical intervention and the time elapsed from the onset of the symptoms to surgery. Methods: 157 medical records of patients from the Pediatric Surgery Service of HNGAI and diagnosed with acute appendicitis complicated with peritonitis were evaluated. The patients were between 2 and 14 years old. They were separated into two groups - 81 open surgeries and 76 laparoscopic. The variables of age, sex, type of surgery, duration of surgery, length of hospitalization and postoperative complications were evaluated. Chi square and Mann-Whitney analysis was used. Results: From the total number of medical records, only 157 medical records met the inclusion criteria, of which 81 appendectomies were open and 76 laparoscopic. Laparoscopic surgery was longer. Complications were more frequent in open surgeries with an incidence of 30.8%, as well as prolonged hospitalization time of 12.7%. Conclusion: Laparoscopic surgeries have a longer duration compared to open surgeries, however, complications and prolonged hospitalization occurred more frequently in open surgeries. This data could be due to the experience of the operator.